Insulin sensitivity as a model-based marker for sepsis diagnosis - Suhaimi F.M.; Chase J.G.; Pretty C.G.; Shaw G.M.; Razak N.; Jamaludin U. (2023)
Diagnosis; Distribution functions; Insulin; Metabolism; Microcirculation; Patient treatment; Cumulative distribution function; High sensitivity; Insulin sensitivity; Metabolic conditions; Model-based OPC; Mortality rate; Patient condition; Real-time diagnosis; Sensitivity analysis